Alopecia Induced by Autologous Fat Injection into the Temporal Area: Case Report and Review of the Literature - Saranya Khunkhet; Teerapong Rattananukrom; Wilai Thanasarnaksorn; Poonkiat Suchonwanit (Karger Publishers, 2019)
Alopecia secondary to facial filler injections is a highly unusual sequela. Only 2 cases of hyaluronic acid-induced alopecia have been reported to date. Accumulating evidence suggests vascular compromise as its etiology, which can be accidental intravascular injection or external compression by overfilled materials. We hereby present, to the best of our knowledge, the first case of localized nonscarring and scarring alopecia secondary to autologous fat grafting and review the literature regarding filler-induced alopecia.